2021
DOI: 10.1177/0309133320986147
|View full text |Cite|
|
Sign up to set email alerts
|

Capability of the variogram to quantify the spatial patterns of surface fluxes and soil moisture simulated by land surface models

Abstract: Up to now, relatively little effort has been dedicated to the quantitative assessment of the differences in spatial patterns of model outputs. In this paper, we employed a variogram-based methodology to quantify the differences in the spatial patterns of root-zone soil moisture, net radiation, and latent and sensible heat fluxes simulated by three land surface models (SURFEX/ISBA, JULES and CHTESSEL) over three European geographic domains – namely, UK, France and Spain. The model output spatial patterns were q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…(The nugget term is negligible for both cases.) The sill and range provide diagnostic quantities in addition to the graphical representation of the variogram that can be utilized in model intercomparisons (see Garrigues et al 2021).…”
Section: The Variogram and Model Intercomparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…(The nugget term is negligible for both cases.) The sill and range provide diagnostic quantities in addition to the graphical representation of the variogram that can be utilized in model intercomparisons (see Garrigues et al 2021).…”
Section: The Variogram and Model Intercomparisonmentioning
confidence: 99%
“…The general problem was that obtaining drill core samples is expensive, and so only a sparse number of samples could be obtained over the field of interest. Kridge and Sichel developed methods for correlating and interpolating sparse samples that are today known as "kriging" and have been applied beyond mining to a wide range of problems, which include weather prediction and geographic information systems as well as climate science (e.g., Drignei 2009;Garrigues et al 2021) and astrophysics (e.g., Tremmel et al 2017). The application of kriging to the analysis of climate models was suggested by Drignei (2009), who demonstrated that sparse samples of computationally expensive GCM calculations can be combined with larger sets of less complex model calculations to make meaningful predictions without needing to run additional GCM cases.…”
Section: Introductionmentioning
confidence: 99%
“…The range parameter thus indicates the range of spatial correlation of the underlying variable [25]. If the value of the range is big, it means that the land cover type has a bigger range of spatial correlation and similar spatial features over a larger distance and vice versa [26][27][28].…”
Section: An Integrated Spatial Landscape Index (Isli)mentioning
confidence: 99%
“…Finally, conclusions were drawn about the dynamic changes of the landscape pattern in the Changbai Mountain National Nature Reserve. means that the land cover type has a bigger range of spatial correlation and similar spatial features over a larger distance and vice versa [26][27][28].…”
Section: An Integrated Spatial Landscape Index (Isli)mentioning
confidence: 99%